Case Report: Recurrence of an Extradural Spinal Epidermoid Cyst Following Surgical Excision in a Dog - Devathasan, Dillon; Murakami, Masahiro; Miller, Margaret A.; Thomovsky, Stephanie A.; Lewis, Melissa J. (Frontiers in Veterinary Science, 2022)
Congenital epidermoid cysts are slow-growing, mass lesions caused by the abnormal inclusion of neuroectodermal tissue within the developing central nervous system. Subtotal excision of epidermoid cysts increases the risk of early recurrence of clinical signs. A 4-year-old female spayed boxer was presented with a 4-month history of ambulatory paraparesis and proprioceptive ataxia. Neurological examination localized a T3-L3 myelopathy. MRI revealed a T1 iso- to hypointense, T2 and FLAIR hyperintense, rim-enhancing mass at the level of the T9-T10 vertebrae resulting in extradural compression of the spinal cord. This was histopathologically confirmed as an extradural epidermoid cyst following subtotal excision. MRI performed 2 months post-operatively revealed a significant decrease of the lesion volume. The dog was neurologically normal following the surgery however re-presented 28 months later with recurrence of clinical signs. A 28-month post-operative MRI revealed substantial enlargement of the epidermoid cyst. The dog was subsequently taken for repeat decompressive surgery. At 6 months from the repeat surgery, the dog was neurologically static with mild proprioceptive deficits. The case report highlights the clinical and MRI features of a recurrent extradural spinal epidermoid cyst treated by subtotal excision.